Mechanical Properties of Steel Fiber-Reinforced Magnesium Phosphate Cement Mortar - Hu Feng; Gang Chen; Danying Gao; Kunpeng Zhao; Chong Zhang (Advances in Civil Engineering)
A new cement-based mortar with high early strength and toughness was developed by adding micro steel fibers (MSF) in magnesium phosphate cement (MPC) mortar. The compressive and flexural tests were carried out to investigate the effect of curing time, MSF volume fraction, sand-cement mass ratio, and water-cement mass ratio on the strength and flexural toughness of MSF-reinforced MPC mortar (MSFRMM). Also, the flexural toughness and ductility of MSFRMM were evaluated according to ASTM C1609. The results of this study showed that the addition of MSF from 0% to 1.6% by volume significantly improved the compressive strength of MSFRMM. The MSFRMM showed high early strength, especially during the first 3 days. The addition of MSFs changed the flexural failure mode of MPC-based mortar from brittleness to ductility, and the flexural toughness of MSFRMM remarkably increased with the increase of MSF volume fraction from 0% to 1.6%. The toughness and ductility of MSFRMM slightly increased with the increase of the dosage of cement. The toughness and ductility of MSFRMM increased with the decrease of the water-cement mass ratio due to the improved density of the mortar caused by the reduction of water.